Duration Of Hypertension And Quality Of Life Of People With Hypertension In Aceh, Indonesia - Harvina Sawitri; Fury Maulina; Yuziani Yuziani (Faculty of Medicine University of Malikussaleh, 2022)
Abstract: Hypertension has affected on a person's quality of life, particularly on elderly people, including their social life, mental health, and psychological function. As a result, the elderly's quality of life will suffer, as will their life expectancy. Objectives: This study aimed to determine the relationship between the duration of hypertension and the quality of life of those who have hypertension. Patients and methods: A descriptive study with a cross-sectional survey was conducted with participants from the Management of Chronic Diseases Program (Prolanis) in primary care in Muara Dua, Lhokseumawe, Aceh, Indonesia. We employed a total sampling technique (35 participants) and collected data through guided interviews using WHOQOL-Bref questionnaires. Results: We discovered that participants with hypertension for less than five years were 45.7%, while those with hypertension for more than five years were 54.3%. Physical domain (57.1%), psychological domain (57.1%), and environmental domain (51.4%) all fall into the